Measuring the reliability and validity of the Greek edition of the Diabetes Quality of Life Brief Clinical Inventory - Rekleiti, Maria; Souliotis, Kyriakos; Sarafis, Pavlos; Tsironi, Maria; Kyriazis, Ioannis (My University, 2018)
Background: The present study focuses on studying the validity and reliability of the Greek edition of DQOL-BCI. DQOL-BCI includes 15 questions-elements that are evaluated on a 5- grade scale like Likert and two general form-shapes. Methods: The translation process was conducted in conformity with the guidelines of EuroQol group. A non-random sample of 65 people-patients diagnosed with diabetes I and II was selected. The questionnaire that was used to collect the data was the translated version of DQOL-BCI, and included the demographic characteristics of the interviewees. The content validity of DQOL-BCI was re-examined from a team of five experts (expert panel) for qualitative and quantitative performance. The completion of the questionnaire was done via a personal interview. Results: The sample consisted of 58 people (35 men and 23 women, 59.9 ± 10.9 years). The translation of the questionnaire was found appropriate in accordance to the peculiarities of the Greek language and culture. The largest deviation of values is observed in QOL1 (1.71) in comparison to QOL6 (2.98). The difference between the standard deviations is close to 0.6. The statistics results of the tests showed satisfactory content validity and high construct validity, while the high values for Cronbach alpha index (0.95) reveal high reliability and internal consistency. Conclusions: The Greek version of DQOL-BCI has acceptable psychometric properties and appears to demonstrate high internal reliability and satisfactory construct validity, which allows its use as an important tool in evaluating the quality of life of diabetic patients in relation to their health.
Keywords: Diabetes; DQOL-BCI; Reliability; Validity